Digital–Green Synergies in Practice: How Emerging and Developed Markets Integrate Technology for Sustainable Value Creation - Sunarno; Diantoro, Karno; Marthalia, Lia (Indonesian Scientific Publication, 2024)
This study examines how digital transformation and green technology adoption jointly influence corporate sustainability. Using frameworks such as the Resource-Based View and dynamic capabilities theory, the research synthesizes empirical evidence to evaluate ESG outcomes, emissions reductions, and operational efficiency. Findings show that digital tools like AI, IoT, and big data significantly enhance the effectiveness of green practices, leading to improved ESG scores, lower emissions, and stronger supply chain resilience. The study concludes that aligning digital and green strategies enables firms to meet stakeholder demands and global sustainability goals while maintaining competitiveness.